2015
DOI: 10.1039/c5nj01645b
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of lanthanide complexes on silica surfaces dehydroxylated at 200 °C: a theoretical investigation

Abstract: Cluster models of SiO 2 -200 are proposed and compared with spectroscopic (IR and NMR) experimental data. Five models describing the variety of surface silanols (isolated, vicinal and germinal) at the SiO 2 -200 surface have then been derived and used to study the grafting reaction of homoleptic silylamide lanthanum(III) complexes. Three different grafting modes have been obtained (mono-, bi-and tri-grafted) in line with the experimental knowledge. In terms of energetic stability as well as spectroscopic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 80 publications
0
19
0
1
Order By: Relevance
“…As in the experimental approaches, some of us have recently described, from ac omputationalp oint of view,t he reactiono fO PPh 3 with different silica-grafted lanthanide species, showingt hat the OPPh 3 coordination strength can be affected by the coordination sphere of the grafted complex. [46,48] To probe the influence of the graphene surface, we have now investigated the OPPh 3 interaction with the graphene grafted hexamethyldisilylamido lanthanum complexesa bove described. The coordination of O= PPh 3 on both the Figure 4b)s pecies through an exothermic process (À28.9 and À24.7 kcal mol À1 ,r espectively).…”
Section: Probing the Lewis Acidity Of Graftedcomplexes:o =Pph 3 Coordmentioning
confidence: 99%
See 2 more Smart Citations
“…As in the experimental approaches, some of us have recently described, from ac omputationalp oint of view,t he reactiono fO PPh 3 with different silica-grafted lanthanide species, showingt hat the OPPh 3 coordination strength can be affected by the coordination sphere of the grafted complex. [46,48] To probe the influence of the graphene surface, we have now investigated the OPPh 3 interaction with the graphene grafted hexamethyldisilylamido lanthanum complexesa bove described. The coordination of O= PPh 3 on both the Figure 4b)s pecies through an exothermic process (À28.9 and À24.7 kcal mol À1 ,r espectively).…”
Section: Probing the Lewis Acidity Of Graftedcomplexes:o =Pph 3 Coordmentioning
confidence: 99%
“…[43][44][45] Combined experimental and theoretical studies on the grafting of lanthanide com-plexes on silica have been recently reported. [46][47][48][49] They show that the formation of ac ovalent SiOÀLn bond requires the presence of hydroxyl groups on the surface, [46] the graftingr eaction of [Ln(N(SiMe 3 ) 2 ) 3 ]( Ln = La Nd, Sm) occurringt hrough a protonolysiso ft he LnÀNb ondb yt he surface silanols. As some of us have previously described, the graftingo famolecular complex on silica surfaces provides as ignificant modification of its catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanides complexes have been grafted onto Si or silica surfaces. [6][7][8][9] Langmuir-Blodgett layers or molecular printboards using -cyclodextrins have been also employed to immobilize lanthanides complexes. 10,11 Immobilization procedure involving anchoring thiols groups have been described onto gold planar surfaces, [12][13][14][15] but also onto gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, esta atividade depende da quantidade de grupos silánóis disponíveis e do seu caráter ácido, assim, a faixa de pH da fase móvel influencia na ionização. Além disso, a atividade silanol também está relacionada ao tipo de silánóis residuais, podendo ser isolado, germinal ou vicinal (Figura 23) (Lesellier e West, 2007;Del Rosal et al, 2015).…”
Section: Atividade Silanolunclassified